Penerapan Media Pembelajaran Inovatif IPA di SDN Sukaasri 01 untuk Siswa Kelas V - Fauziah, Syifa; Salsabila, Humaira Azka; Sulistiawati, Ika (Indonesian Journal Publisher, 2023)
Learning media is an instrument used by teachers to achieve their learning goals and contains learning messages. In particular, learning media is a tool to convey feelings, ideas, and the desire for students to actively participate in the learning process to achieve more effectively and efficiently. The research used qualitative research because data collection comes from the intended subject. The data collection of this research is an interview giving questions to the teacher. Learning media in the 2013 curriculum and the independent curriculum have the same characteristics, namely learning media must be involved in student life. The use of science learning media must be adapted to student learning materials.